2022
DOI: 10.1111/ans.18078
|View full text |Cite
|
Sign up to set email alerts
|

The utility of ctDNA in colorectal cancer with peritoneal metastases

Abstract: Background The development of peritoneal metastases (PM) in patients with colorectal cancer (CRC) connotates a poor prognosis. Circulating tumour (ctDNA) is a promising tumour biomarker in the management CRC. This systematic review aimed to summarize the role of ctDNA in patients with CRC and PM. Methods Following the Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) guidelines, a systematic review of the literature until June 2022 was performed. Studies reporting on the utility of ct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Xue et al performed a systematic review on the utility of ctDNA in CRC PM, including eight studies with 167 patients. The authors not only found that ctDNA can be isolated from both plasma and peritoneal fluid, but peritoneal fluid had higher mutation detection rates and was preferred for liquid biopsy [ 40 ]. Furthermore, as compared to patients with CRC PM, patients with CRC liver metastases have higher detectable ctDNA.…”
Section: Influence Of Site Of Metastasis On Ctdnamentioning
confidence: 99%
“…Xue et al performed a systematic review on the utility of ctDNA in CRC PM, including eight studies with 167 patients. The authors not only found that ctDNA can be isolated from both plasma and peritoneal fluid, but peritoneal fluid had higher mutation detection rates and was preferred for liquid biopsy [ 40 ]. Furthermore, as compared to patients with CRC PM, patients with CRC liver metastases have higher detectable ctDNA.…”
Section: Influence Of Site Of Metastasis On Ctdnamentioning
confidence: 99%
“…Research has shown that in the advanced disease setting, data highlight the potential of circulating tumor DNA (ctDNA) levels as a prognostic marker and as an early indicator of treatment response. ctDNA assessment can complement standard tissue-based testing for molecular characterisation, with the added ability to monitor emerging mutations under the selective pressure of targeted therapy, they provide an overview of the evidence supporting the use of ctDNA in CRC ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%